Systematic review of university public relations communication strategies: 2010–2022 - Majid, Abd; Wahyuni, Hermin Indah; Abrar, Ana Nadhya; Fitrah, Andi Awaluddin (PRofesi Humas, 2025)
Background: Global South colleges employ public relations differently. This gap must be researched to improve these institutions’ reputations. This paper maps and analyzes university public relations research and evaluates science communication framework integration. Method: A comprehensive literature study of four main public relations journals examined publication frequency on public relations, universities, higher education, and colleges during the past 12 years. Results: Public relations research has increased, although university-related studies are scarce. Only twenty-one articles explored this sector, mostly by US scholars focusing on crisis communication. These findings reveal higher education institutions’ communication dynamics and goals when analyzed organizationally and systemically. This report discusses university branding, digital communication methods, and stakeholder participation. It also reveals temporal patterns, such as communication practice changes over time, and university communication components like crisis management and community engagement. These factors depart from public relations research’s corporate and governmental focus. Conclusion: University-specific public relations literature is lacking due to crisis communication studies and US-based authors. This emphasizes the need for further research, particularly the incorporation of the science communication framework, which is essential for understanding how higher education institutions communicate with the public on scientific matters. Implications: This study suggests universities use communication tactics that differ from commercial and government public relations studies.